The technological role of inward foreign direct investment in Central East Europe - Stephan, Johannes; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
Foreign direct investment (FDI) assumed a prominent role in Central East Europe (CEE) early on in the transition process. Foreign investors were assigned the task of restructuring markets, providing capital and knowledge for investment in technologically outdated and financially ailing firms.
Keywords: Investment banking; Securities; Microeconomics; Macroeconomics; International economics; Development economics; Regional economics; Spatial economics